Analysis of Factors Related to National Health Insurance Participation in Rungan Barat District - Wilson Wilson; Zairin Noor; Muhammad Abdan Shadiqi; Silvia Kristanti Tri Febriana; Bahrul Ilmi (Lambung Mangkurat, 2024)
Target of the 2020-2024 RPJMN is targeting NHI membership of 98%. The data shows that West Rungan District is the area with the lowest coverage in Gunung Mas Regency as 36.35% in 2022. The study purposed to analyze the factors related to National Health Insurance membership in West Rungan District. The study used an analytic survey method with a cross sectional design. The population of this research is the people who live in West Rungan District, Gunung Mas Regency with a sample of 109 people who were determined using non-probability sampling with accidental sampling technique. Data were taken from primary data using a questionnaire. Data were analyzed by chi square test and multiple logistic regression. The chi square test shows the p-value between family income (p=0.001 < α 0.05), level of knowledge (p=0.323 >α 0.05), level of education (p=0.062 >α 0.05), number of family members (p=0.751 >α 0.05) and registration procedures (p=1,000 >α 0.05) with JKN participation. The conclusion was that there was a relationship between family income and NHI membership in West Rungan District. There was no significant relationship between family income, level of knowledge, level of education, number of family members, and registration procedures and NHI membership. Logistic Regression Test shows that family income is the most dominant factor (OR=6.536) related to JKN participation in West Rungan District.